2021
DOI: 10.3390/app11188766
|View full text |Cite
|
Sign up to set email alerts
|

Declining Effect of Precipitation on the Normalized Difference Vegetation Index of Grasslands in the Inner Mongolian Plateau, 1982–2010

Abstract: Grasslands play an irreplaceable role in maintaining carbon balance and stabilizing the entire Earth’s ecosystem. Although the grasslands in Inner Mongolia are sensitive and vulnerable to climate change, a generalized effect of climate change on the grasslands is still unavailable. In this study, we analyzed the effects of annual mean precipitation and annual mean temperature on the normalized difference vegetation index from 1982 to 2010 on the Inner Mongolia Plateau. Our results indicated that the normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Similarly, this phenomenon has been mentioned in previous studies, such as Hsu et al [1] who found that changes in the inter-annual variability of precipitation had negligible effects on the mean ANPP. On the contrary, Li et al [55] highlighted that the NDVI is adaptable to the significant increase in temperature but is sensitive to the decrease in precipitation on the Inner Mongolia Plateau, possibly due to regional differences. In addition, VST and VSP in the different seasons showed significant dynamic change at the scale of space-time (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, this phenomenon has been mentioned in previous studies, such as Hsu et al [1] who found that changes in the inter-annual variability of precipitation had negligible effects on the mean ANPP. On the contrary, Li et al [55] highlighted that the NDVI is adaptable to the significant increase in temperature but is sensitive to the decrease in precipitation on the Inner Mongolia Plateau, possibly due to regional differences. In addition, VST and VSP in the different seasons showed significant dynamic change at the scale of space-time (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, R 2 is often used to study the influence of climate on vegetation dynamics. For example, it has been used to analyze the effects between the NDVI and climate, and reflect the effect of the climate on net primary production [52,55]. In addition, compared with the previous calculation method of VSP and VST by least squares [1,38], the spatial heterogeneity of VSP and VST was reduced in the updated method because it fragmented the space by dividing the Tibetan Plateau into many small plots, on average, to discuss the sensitivity of vegetation to precipitation and temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum NDVI performed better than other NDVI metrics, indicating that the differentiation between bamboo and other vegetation is more obvious during the growing seasons. It may be related to the fact that NDVI is sensitive to changes in precipitation and temperature [79,80]. Additionally, elevation was ranked fourth in the importance score [25].…”
Section: Feature Importancementioning
confidence: 99%
“…Climate change and its impact on terrestrial ecosystems have attracted widespread attention (Bao et al, 2014). Globally, CO 2 fertilization is the main driver of the vegetative greenness, with other factors including anthropogenic warming, precipitation, and solar radiation that are dominant drivers of the vegetation growth at regional scales (Li et al, 2021;Bai et al, 2022). In high latitudes and high altitudes where temperature is usually a limiting factor, global warming has a positive impact on vegetation growth, especially for ecosystems at high latitudes, and increasing air temperature promotes photosynthesis of vegetation (Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%